To Stretch the Boundary of Secondary Metabolite Production in Plant Cell-Based Bioprocessing: Anthocyanin as a Case Study. Issue 5 (1st December 2004) - Zhang, Wei; Franco, Chris; Curtin, Chris; Conn, Simon
Abstract : Plant cells and tissue cultures hold great promise for controlled production of a myriad of useful secondary metabolites on demand. The current yield and productivity cannot fulfill the commercial goal of a plant cell-based bioprocess for the production of most secondary metabolites. In order to stretch the boundary, recent advances, new directions and opportunities in plant cell-based bioprocessing, have been critically examined for the 10 years from 1992 to 2002. A review of the literature indicated that most of the R&D work was devoted predominantly to studies at an empirical level. A rational approach to molecular plant cell bioprocessing based on the fundamental understanding of metabolic pathways and their regulations is urgently required to stimulate further advances; however, the strategies and technical framework are still being developed. It is the aim of this review to take a step forward in framing workable strategies and technologies for molecular plant cell-based bioprocessing. Using anthocyanin biosynthesis as a case study, an integrated postgenomic approach has been proposed. This combines the functional analysis of metabolic pathways for biosynthesis of a particular metabolite from profiling of gene expression and protein expression to metabolic profiling. A global correlation not only can thus be established at the three molecular levels, but also places emphasis on the interactions between primary metabolism and secondary metabolism; between competing and/or complimentary pathways; and between biosynthetic and post-biosynthetic events.